Study on realtionship between seed germination and antioxidant enzyme activity - J, Bayarmaa; D, Purev (Mongolian Journal of Agricultural Sciences, 2019)
Success in plant cultivation is related to seed production and germination. Seed germination and seedlings are well-regulated process which involves high metabolic activity and production of reactive oxygen species (ROS) in cell. However, plant POS defense network, composed of antioxidant enzymes and antioxidants are responsible for maintaining ROS levels under control. In plant cells, antioxidant enzymes as superoxide dismutase (SOD), peroxidase (POD), catalase (CAT) and others protect cells from oxidative damage during germination and growth. Thus, in this work we studied the content of soluble protein and the activity of enzymes as catalase, peroxidase, polythenol oxidase (PPO) and superoxide dismutase in two cultivars of wheat, barley and oat seeds differing in germination and year of harvesting. The results showed that the activities of antioxidant enzymes and seed germination are directly dependent and this relation clearly seen for catalase and peroxidase activity. Үрийн соёолох чадвар ба исэлдэн-ангижрах ферментийн идэвх хоорондын хамаарлыг судалсан дүн Хураангуй: Тариалсан он болон соёололтоороо ялгаатай улаан буудай, арвай, овъёосны үрийн дээжинд уусдаг уураг, исэлдэн-ангижрах ферментүүд болох каталаза, пероксидаза, полифенолоксидаза (ПФО), супероксиддисмутаз(СОД)-ын идэвхийг тодорхойлов. Судалгаагаар ферментийн идэвх соёололтын хэмжээтэй шууд хамааралтайбуюукаталаза, пероксидаза фермент нь үрийн соёололттой ПФО, СОД ферменттэй харьцуулахад илүү хамааралтай байж болох үр дүнг үзүүлэв. Түлхүүр үг: Буудай, арвай, овъёос, сорт